Enabling the Transition to a Circular Economy: A Literature Review on Stakeholder Collaboration - Sitio, Rike Penta; Jahroh, Siti; Harianto, Harianto; Suprehatin, Suprehatin (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study explores the interaction among stakeholder in promoting the transition of businesses from conventional models to circular economy practices. By conducting an extensive literature review of 122 articles from the Scopus database, this research utilizes bibliometric and content analysis to identify significant trends and themes. Over the years, research on the transition toward circular economy practices has increased significantly, growing from a single publication in 2016 to 42 in 2024. The United Kingdom, Germany, and China have emerged as leading contributors to this field, reflecting a global interest in sustainable business transformation. Bibliometric analysis identified four dominant cluster areas: 1) Collaboration and sustainability; 2) Innovation and business model development; 3) Resource management and recycling; 4) Product lifecycle and circular value chain. Findings suggest that a successful transition to a circular economy depends on close collaboration between governments, businesses, and consumers, with technology acting as a key enabler. Notably, consumer awareness and engagement play a critical role in encouraging businesses to embrace circular practices. Without strong partnership among businesses, policymakers, consumer, and other actors, achieving long-term success in circular economy practices would be challenging.